Soil Moisture Differences Between Continues Measurements of Three Crop Managements - Putri, Elsa Lolita; Hermawan, Bandi; Agustian, Indra; Hasanudin (TERRA : Journal of Land Restoration, 2023)
Soil moisture prediction models on a regional scale can be developed by looking for the relationship between water balance and basic soil properties such as texture and organic matter.  Our previous research has obtained soil dielectric properties measurement technology as an estimator of soil moisture that can be done quickly in the field. The purpose of this study was to apply this technology in estimating the characteristics of soil moisture insitu in the field on a district scale in Bengkulu Province.  The research was conducted for three years in three different districts in Bengkulu Province. The results of the third year to early October 2021 study showed that land under thicket stands and oil palm had higher weekly groundwater fluctuations than under rubber. The highest impedace of groundwater below the thickets and palms are present at depths of 0-20 cm and 0-10 cm, respectively.  However thickets have fluctuations in the depth of total groundwater (0-30 cm depth) that are higher than those of oil palms during three months of measurement.  In contrast, the soil moisture content profile under the rubber stand is relatively more stable against the influence of weekly rainfall during the measurement. An analysis of the relationship between non-free variables (field capacity moisture content, permanent wilting point and water available) and free variables (sand, dust, clay and C-organic) will be carried out in November 2021